A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus. Issue 7 (8th August 2020) - Peng, Li-Hua; Liang, Xiao; Chang, Rui-Heng; Mu, Jia-Yi; Chen, Hui-E; Yoshida, Asami; Osatomi, Kiyoshi; Yang, Jin-Long
Abstract: Larval settlement and metamorphosis is essential for the development of marine invertebrates. Although polysaccharides are involved in larval settlement and metamorphosis of Mytilus coruscus, the molecular basis of polysaccharides underlying this progression remains largely unknown. Here, the roles of the polysaccharide biosynthesis-related gene 01912 of Pseudoalteromonas marina ECSMB14103 in the regulation of larval settlement and metamorphosis were examined by gene-knockout technique. Compared with biofilms (BFs) of the wild-type P. marina, Δ 01912 BFs with a higher colanic acid (CA) content showed a higher inducing activity on larval settlement and metamorphosis. Deletion of the 01912 gene caused an increase in c-di-GMP levels, accompanied by a decrease in the motility, an increase in cell aggregation, and overproduction of CA. Thus, the bacterial polysaccharide biosynthesis-related gene 01912 may regulate mussel settlement by producing CA via the coordination of c-di-GMP. This work provides a deeper insight into the molecular mechanism of polysaccharides in modulating mussel settlement.